Studies on Serum Total Cholesterol, in Second and Third Trimester of Pregnancy - Husain, F; Latif, SA; Uddin, MM (Journal of Bangladesh Society of Physiologist, 2008)
Study was carried out in the department of physiology, Mymensingh Medical College, Mymensingh, Bangladesh during the period of July 2006 to June 2007 to investigate the effect of pregnancy on serum total cholesterol. The serum concentrations of total cholesterol was measured in 100 cases of 2nd and 3rd trimester of pregnancy and in a control group of 100 cases of non pregnant women which was matched on reproductive age. Data were analyzed by computer with SPSS program using unpaired studentt test. The results showed that the pregnant women had significantly higher concentrations of serum total cholesterol. Higher concentration of total cholesterol was more common in pregnant than control and reaching maximum at 3rd trimester of pregnancy. This may be a purely physiological response to pregnancy or it may be indicative of pathology in some women. These results deserve a follow up study to investigative whether the hypercholesterolemia persists after parturition. Key Words: Total cholesterol, pregnancy, parturition, hypercholesterolemia J Bangladesh Soc Physiol. 2006 Dec;(1):1-4.